2021
DOI: 10.1590/1980-220x-reeusp-2021-0138
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of psychoactive substance use: a comparative study of two services in Brazil and Portugal

Abstract: Objective: To compare the consequences of psychoactive substance use among users of mental health services in Brazil and Portugal. Method: Cross-sectional, comparative, quantitative study, carried out with 362 users of two specialized treatment services in the cities of São Paulo (n = 200) and Lisbon (n = 162). Data collected in 2019 through the application of the Substance Addiction Consequences scale. A descriptive analysis and ordinary least squares and logistic regressions were performed. Results: All di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Psychoactive substance use has become a major public health and socioeconomic problem worldwide (7). It results in physical, social, and mental health disorders (8,9). Different studies indicated that psychoactive substance users are at risk to develop cancer, heart diseases, and sexually transmitted diseases including HIV, anxiety disorder, bipolar disorder, and antisocial personality disorder (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Psychoactive substance use has become a major public health and socioeconomic problem worldwide (7). It results in physical, social, and mental health disorders (8,9). Different studies indicated that psychoactive substance users are at risk to develop cancer, heart diseases, and sexually transmitted diseases including HIV, anxiety disorder, bipolar disorder, and antisocial personality disorder (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Várias drogas são encontradas em nossa sociedade de forma ilegal, por isso denominada ilícitas, cocaína, crack, heroína, dentre outras 11 . Há correlação de doenças, desempregos, crimes e mortes, contudo, é imensurável os danos, custos emocionais e sociais da dependência química para o indivíduo e sociedade 10 .…”
Section: Introductionunclassified
“…In Brazil, the legitimation and institutionalization of these practices in health care began in the 1980s, after the creation of the SUS. Among the integrative practices, the techniques included within Traditional Chinese Medicine (TCM) stand out, such as: acupuncture, herbal medicine and shiatsu [6], which are considered effective therapies for anxiety control and with better cost-benefit compared to to the side effects caused by benzodiazepines [7].…”
Section: Introductionmentioning
confidence: 99%